Job Satisfaction and Psychological Well-Being as Employee Performance Factors in Educational Institutions - Pudjiati Pudjiati; Saida Zainurrossalamia ZA; Dirga Lestari A.S (IJEBD (International Journal of Entrepreneurship and Business Development), 2023)
Purpose: This study aims to determine the factors that affect employee performance in higher education, consisting of job satisfaction and psychological well-being, where to produce high performance requires positive employee job satisfaction as well as the psychological well-being of employees in the institutional environment. Design/methodology/approach: The research used in this study is quantitative research Findings: There is a significant influence of job satisfaction and psychological well-being on employee performance at universities in Balikpapan or hypothesis 1 is accepted. good job satisfaction will result in good performance as well and Good psychological well-being at work is when individuals have motivation, are involved in a job, have positive energy, feel happy with all the activities undertaken and last long at the job they are currently doing. Paper type: Research paper